Controversy over the Round Earth and the Flat Earth on the Interpretation of the Qur'an: Study Interpretation with a Scientific Approach - Muttaqin, Rofi; Hakim, Dzikri; Fadilahi, Salman; Rafsanjani, Muhammad; Mubarok, Ade Sobur; Muhaimin, Ujang Mimin (Institut Agama Islam Persis Bandung, 2022)
Abstract[Controversy over the round earth and the flat earth on the interpretation of the Qur’an: study interpretation with a scientific approach] This article discusses the interpretation related to the Qur'anic verses about the round and flat earth, through a scientific approach (bil ilmi) this study uses a qualitative method of comparative studies with shorts. The data source is the book